TINGKAT PEMANFAATAN UDANG KARANG (Panulirus spp) BERDASARKAN PENDEKATAN MODEL PRODUKSI SURPLUS DI PERAIRAN KABUPATEN PANGKEP - Hasrun Hasrun; Kasmawati Kasmawati; Muhammad Jamal Alwi (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2023)
Crayfish (Panulirus spp) is one type of Indonesian marine fishery resources that is very potential and has long been caught by fishermen in coral areas to find out the description of fishing gear, methods, and crayfish fishing areas (Panulirus spp) in the waters of Pangkep Regency and to find out the estimated utilization rate of crayfish using the MSY approach in Pangkep Regency. This research has been carried out by taking data in the form of primary data carried out from March 1, 2022 – April 30, 2022 and secondary data in the form of catch production data and fishing efforts (units) obtained from the Marine and Fisheries Service of Pangkep Regency for the 2016-2021 time period. The results of this study showed that the fishing gear used to catch crayfish (Panulirus spp) was a fixed gill net using a canoe boat as a tool. The process of catching crayfish includes setting, soaking and hauling. Coral fishing grounds are in rocky areas with the fishing season occurring from November to January. Based on the results of research using three surplus production models, it was concluded that the most suitable surplus production model for crayfish fisheries in Pangkep Regency is the Gulland model by showing a large (R2) and a small standard deviation. The maximum sustainable catch is 16,783.58 kg/year and the attempted catch is 12,496 units. The Utilization Rate (TP) and Capability Rate (TPU) have exceeded (yJTB) and (fJTB) with overexploited status.